The analysis of Japanese fairy tales using propp’s structural-typological narratives by Japanese language learners - Musaev, Talaibek; Jamaluddin Aziz,; Jamila Mohd, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Fairy tales reflect the great social values of certain cultures. Individual genres and works of fairy tales represent projections of the worldview of people in the respective society. However, reading and understanding fairy tales from other countries are not enough to identify structural and typological differences between tales of the same genre that differ in origin. In literature classes, students often focus on the narrative while missing the structural features of fairy tales. In this study, the structural-typological functions of narrative proposed by Propp (1986) were used as a methodological approach to draw students’ attention to the distinctive cultural features of some Japanese fairy tales. The results show that students classified Japanese tales as differing greatly in structural and typological variation compared to European tales. Students realized that in Japanese fairy tales, the ending does not always lead the hero to the typical victory of good over evil, but sometimes leaves a certain bitterness of reality where the ending is guessed by the reader, which gives the tale a debatable narrative character that is unique. This methodological approach helps students analyse fairy tales in greater depth, identify the uniqueness of the narratives, and delve into the essence of structural and functional analysis, which gives students a deep understanding of the tales and its culture. The findings of this study can be applied to the identification of the functions and roles of the characters in fairy tales, and the analysis of structured storylines.